IL-22 regulates endometrial regeneration by enhancing tight junctions and orchestrating extracellular matrix - Ganieva, Umida; Schneiderman, Sylvia; Bu, Pengli; Beaman, Kenneth; Dambaeva, Svetlana (Frontiers in Immunology, 2022)
Uterine endometrium uniquely regenerates after menses, postpartum or after breaks in the uterine layer integrity throughout women’s lives. Direct cell-cell contacts ensured by tight and adherens junctions play an important role in endometrial integrity. Any changes in these junctions can alter endometrial permeability of the uterus and have an impact on the regeneration of uterine layers. Interleukin 22 (IL-22) is a cytokine that is recognized for its role in epithelial regeneration. Moreover, it is crucial in controlling the inflammatory response in mucosal tissues. Here, we studied the role of IL-22 in endometrial recovery after inflammation-triggered abortion. Fecundity of mice was studied inconsecutive matings of the same animals after lipopolysaccharide (LPS) (10 µg per mouse) triggered abortion. The fecundity rate after the second mating was substantially different between IL-22 knockout (IL-22-/-) (9.1%) and wild type (WT) (71.4%) mice (p<0.05), while there was no difference between the groups on initial mating, suggesting that IL-22 deficiency might be associated with secondary infertility. A considerable difference was observed between IL22-/-and WT mice on the uterine clearance following LPS-triggered abortion. Gross examination of the uteri of IL22-/- mice revealed non-viable fetuses retained inside the horns (delayed clearance). In contrast, all WT mice had completed abortion with total clearance after LPS exposure. We also discovered that IL-22 deficiency is associated with a decreased expression of tight junctions (claudin-2 and claudin-10) and cell surface pathogen protectors (mucin-1).Moreover, IL-22 has a role in the remodeling of the uterine tissue in inflammatory environment by regulating epithelial-mesenchymal transition markers called E- and N-cadherin. Therefore, IL-22 is contributing to the proper regeneration of endometrial layers after inflammation-triggered abortion. Thus, it might have a practical significance to be utilized as a treatment option postpartum (enhanced regeneration function) and in secondary infertility caused by inflammation (enhanced barrier/protector function).